Field emergence and the long‐term efficacy of control of Heracleum sosnowskyi plants of different ages in southern Poland. (6th July 2016) - Klima, K; Synowiec, A
Summary: Heracleum sosnowskyi is one of the three so‐called tall or giant hogweeds currently invading Asia, Europe and North America. These plants are dangerous invasive weeds, causing severe skin injuries in humans and animals. In the present study, based on four field experiments, we assessed seedling emergence in the field and evaluated methods for the long‐term mechanical and chemical control of H. sosnowskyi of various ages (1–5 years old). The field experiments were set up in the mountainous regions of southern Poland, on soil not previously infested with H. sosnowskyi seeds. The results showed that the successful eradication of this species from an invaded area is possible. The results revealed that when no new flush of seeds is delivered to the soil seedbank, the longevity of H. sosnowskyi seeds is approximately five years, with the majority of seedlings emerging in the spring of the first year following sowing. Long‐term shoot cutting, particularly the intensity of this technique, is ineffective for the control of H. sosnowskyi . Cutting three times a year for five years resulted in an H. sosnowskyi control outcome of 42–97%. Total control of this weed is obtained either by cutting the roots of plants up to 5 years old at a depth of 15 cm or by continuous (5 years long) herbicide spraying three times during the vegetative season, using a tank mixture of glyphosate and flazasulfuron (1260 g a.i. glyphosate ha −1 + 50 g a.i. flazasulfuron ha −1 ).